2021
DOI: 10.3389/fonc.2021.744331
|View full text |Cite
|
Sign up to set email alerts
|

Glia Maturation Factor Beta as a Novel Biomarker and Therapeutic Target for Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common types of cancer. The novel sensitive biomarkers and therapeutic targets are urgently needed for the early diagnosis of HCC and improvement of clinical outcomes. Glia maturation factor-β (GMFB) is a growth and differentiation factor for both glia and neurons and has been found to be tightly involved in inflammation and neurodegeneration conditions. In our study, the expression level of GMFB was significantly up-regulated in patients with HCC and positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…OS analysis showed that Gmfb expression was negatively correlated with the hazard ratio (HR) of KIRC but positively correlated with the HR of LIHC in pan-cancers (Figure 1A). This was consistent with a previous report (24), in which Gmfb expression was negatively correlated with the HR of KIRC but positively correlated with the HR of adrenocortical carcinoma (ACC) (Figure 1A). Based on the correlation of Gmfb with OS and DFS in pan-cancer analysis, GMFB may be a promising novel prognostic factor for KIRC.…”
Section: Survival Atlas Of Gmfb In Multiple Cancer Types and Differen...supporting
confidence: 93%
See 4 more Smart Citations
“…OS analysis showed that Gmfb expression was negatively correlated with the hazard ratio (HR) of KIRC but positively correlated with the HR of LIHC in pan-cancers (Figure 1A). This was consistent with a previous report (24), in which Gmfb expression was negatively correlated with the HR of KIRC but positively correlated with the HR of adrenocortical carcinoma (ACC) (Figure 1A). Based on the correlation of Gmfb with OS and DFS in pan-cancer analysis, GMFB may be a promising novel prognostic factor for KIRC.…”
Section: Survival Atlas Of Gmfb In Multiple Cancer Types and Differen...supporting
confidence: 93%
“…FP205-02, Tiangen Biotech, Beijing, China) were used for conducting qRT-PCR on a LightCycler 96 Detection System (Bio-Rad Laboratories, Hercules, CA, USA). Data were analyzed using the 2 −ΔΔCt method ( 24 ). Oligos were synthesized by Sangon Biotech.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations